Rotation of single crystals of chiral dopants at the top of namatic droplet: a hydrodynamical analogy - Gvozdovskyy, I.A.; Lisetski, L.N. (Functional Materials, 2007)
In the Lehmann-type effect of rotation of small single crystals of chiral substances during their dissolution at the top of a nematic droplet the angular velocity of rotation of the chiral dopant crystals is experimentally shown to be dependent on the crystal dimensions, helical twisting power of the dopant (determined in independent measurements) and viscosity of the nematic solvent, whereas no rotation was observed for non-chiral dopants or in isotropic solvents under the same conditions. For systematic series of dopants (e.g., cholesterol esters), linear dependencies between the angular velocity and helical twisting power were found. It is argued that the obtained results (a) suggest a novel method for evaluation of helical twisting power, especially useful for dopants of weak chirality, and (b) are a direct evidence of transformation of the energy of chiral interactions into the energy of molecular movement.